Irrigation: Water, soil and data - Lukhele, Doctor (Technical Centre for Agricultural and Rural Cooperation, 2010)
A project in Swaziland uses remote sensing and GIS to identify irrigable farmland. The data are analysed to improve the efficiency of project management processes